ISLAMIC EDUCATION AS THE SPIRITUAL AND MORAL FOUNDATION OF THE YOUNG GENERATION - Mitra Sasmita; Agus Fudholi; Rahma Dilla Zainuri (CV. ADIBA AISHA AMIRA, 2024)
The Islamic education system is central to the cultivation of values in young people especially given the present day modernisation and globalisation. In this particular study, the research approach adopted is that of literature review. The results showed that; (1) Integrating good moral values and ethics with Islamic teachings, (2) Preserving and self-affirming the spiritual core amidst global diaspora, (3) Outlining proper boundaries in contemporary moral issues, (4) Enhancing spiritual intelligence aside from emotional and intellectual intelligence. Some of the major challenges that have been reported are, the media and technological negatives, the secularized nature of education, and the disconnect between religion and education. Possible ways for improvement are: the adoption of a more comprehensive curriculum reform, enhancement of teachers’ skill levels, the integration of information technology in the teaching process, and the promotion of collaboration among educational establishments, parents, and society. Thus, Islam education has a great promise in producing well-rounded morally upright and strong minded young individuals. And to enhance the relevance and efficacy of purpose of Islamic education in developing young people on the various aspects needed to be competitive in the future is to introduce the education into its current context.